Sustainable metal recovery from spent lithium-ion battery using electrochemical technique: A comprehensive method review - Sayali Apte; Aparna Mukherjee; Preeti Mishra (MethodsX)
The pervasive presence of Spent Lithium-Ion Batteries (S-LIB) poses a significant environmental threat due to their hazardous components and the resource-intensive mining of scarce metals like lithium, cobalt, and nickel. Efficient recycling offers a solution by fostering a circular economy and mitigating the environmental impact of disposal and primary resource extraction. Electrochemical recycling (ECR) has emerged as a promising sustainable technology for recovering scarce metals and promoting the circular economy.The paper discusses methods for ECR of S-LIBs, emphasizing the latest developments targeting the increasing demand for critical metals. The U.S. patent data available through January 2025 is accessed from the Lens database using different keywords. Focusing on the latest and highly cited patents, the paper establishes benefits, drawbacks, research gaps, and future scopes in the domain of ECR.Higher selectivity, reduced energy usage, less environmental footprint, increased recovery rates, and possibilities of electrolyte regeneration appeared as some strengths of electrochemical techniques. However, challenges like process complexity due to multi-element systems, employment of strongly corrosive solvents, membrane fouling, and scalability are also witnessed. Future work must aim to improvise the electrochemical recovery system using high-performance anodes, decrease corrosiveness to enhance the electrode durability, and improve membrane performance to make scalable, cost-efficient, and environmentally friendly electrochemical recovery of high-purity metals from S-LIBs.